Development of a coal shrinkage?swelling model accounting for water content in the micropores. (20th November 2009) - Thararoop, Prob; Karpyn, Zuleima T.; Ertekin, Turgay
Changes in cleat permeability of coal seams are influenced by internal stress, and release or adsorption of gas in the coal matrix during production/injection processes. Coal shrinkage?swelling models have been proposed to quantify such changes; however none of the existing models incorporates the effect of the presence of water in the micropores on the gas sorption of coalbeds. This paper proposes a model of coal shrinkage and swelling, incorporating the effect of water in the micropores. The proposed model was validated using field permeability data from San Juan basin coalbeds and compared with coal shrinkage and swelling models existing in the literature.